High Prevalence of Abnormal Ocular Surface Tests in a Healthy Pediatric Population - Rojas-Carabali W (Dove Medical Press, 2020)
William Rojas-Carabali,1 Pilar Uribe-Reina,1,2 Juliana Muñoz-Ortiz,2 Juan Pablo Terreros-Dorado,2 María Eugenia Ruiz-Botero,1 Nicolás Torres-Arias,1 Juliana Reyes-Guanes,2 Alejandra Rodriguez Zarante,1 Jose Y Arteaga-Rivera,2 Camilo Mosos,2 Ángela María Gutiérrez,2 Nicolás Molano-González,3 Guillermo Marroquín,4 Alejandra de-la-Torre1 1Research Group in Neurosciences NeURos. Escuela de Medicina y Ciencias de la Salud, Universidad del Rosario, Bogotá, Colombia; 2Escuela Barraquer. research group. Escuela Superior de Oftalmología del Instituto Barraquer de América, Bogotá, Colombia; 3Clinical Research Group. Escuela de Medicina y Ciencias de la Salud, Universidad del Rosario, Bogotá, Colombia; 4Horus Grupo Oftalmológico, Bogotá, ColombiaCorrespondence: Alejandra de-la-TorreNeURos Research Group, Escuela de Medicina y Ciencias de la Salud, Universidad del Rosario, Carrera 24 # 63C 69, Bogotá, ColombiaTel +57 1 2970200 ext. 3320Email alejadelatorre@yahoo.comPurpose: To describe ocular surface characteristics and tests’ results in a healthy pediatric population.Methods: We performed a cross-sectional study with 60 healthy children, obtaining consent, OSDI and screen use survey and conducting ocular surface tests. Statistical univariate analysis for categorical and quantitative variables was made. To describe the correlation of the results in both eyes, we used a model of random effects. To characterize the possible profiles of device use, we applied the mixed-cluster methodology.Results: Sixty healthy children between 7 and 17 years old were evaluated. Girl’s proportion was 41.6%. Mean Ocular Surface Disease Index Score was 9.98± 8.49 points. Daily screen time was 5.59± 2.77 hours and the most popular screen was the smartphone. Mean results (with standard deviations or confidence intervals) of ocular surface tests were blink frequency while reading on paper, 6.8± 5.68 times per minute; blink frequency while reading on screen, 8.7± 7.14 times per minute; tear meniscus height, 0.19[0.18– 0.2] mm; non-invasive tear break-up time, 12.44[10.99– 13.9] seconds; nasal conjunctival redness, 0.86[0.77– 0.94]; temporal conjunctival redness, 0.96[0.87– 1.04]; tear osmolarity, 299.3[295.14– 303.45] mmol; and Schirmer test, 23.73[21.28– 26.18] mm. Lid margin was irregular in three eyes; 44.7% had thin lipid layer; lissamine green staining was positive in 70.8%; fluorescein staining was positive in 47.4%; 36.64% exhibited partial meibomian gland loss.Conclusion: Considering the scarcity of specific pediatric values of ocular surface tests, we performed a clinical investigation involving the complete pool of ocular surface tests in children. Although healthy children were included in this study, we found that all the participants had at least one abnormal result and 33.33% had dry eye disease diagnosis, according to the TFOS DEWS II. It would be relevant to carry out further multicentric studies to compare our ocular surface tests’ results with other groups of children.Keywords: adolescent, children, dry eye syndrome, ocular surface tests